1996
DOI: 10.1093/oxfordjournals.ndt.a027143
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte sedimentation rate, an underestimated tool in chronic renal failure

Abstract: We conclude that erythrocyte sedimentation rate can be used in haemodialysis patients much in the same way as in the general population, as it is influenced by the same factors, and its baseline value is lower than previously reported. The lower concentration of fibrinogen, an independent predictor of cardiovascular risk, in patients treated with biocompatible membranes may be of clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…This chronic vascular injury might result in low compliance and leaking of the vessels, predisposing to both asymptomatic (microbleed) hemorrhage and sICH. Elevated ESR levels can be seen in patients with chronic kidney disease 32,33 ; however, there was no collinearity between the two in our population. Given the apparent association between elevated ESR and intracerebral hemorrhage, additional studies with pathological correlation to determine the underlying pathophysiologic mechanisms are needed.…”
Section: Discussionmentioning
confidence: 49%
“…This chronic vascular injury might result in low compliance and leaking of the vessels, predisposing to both asymptomatic (microbleed) hemorrhage and sICH. Elevated ESR levels can be seen in patients with chronic kidney disease 32,33 ; however, there was no collinearity between the two in our population. Given the apparent association between elevated ESR and intracerebral hemorrhage, additional studies with pathological correlation to determine the underlying pathophysiologic mechanisms are needed.…”
Section: Discussionmentioning
confidence: 49%
“…ESR has seldom been studied in patients on HD 19 . To the best of our knowledge, ESR has not previously been mentioned as a CV risk factor in this patient population.…”
Section: Discussionmentioning
confidence: 88%
“…Since then, there have been only a few reports on the ESR in this population [3, 4, 5, 6]. All of them, except one [5], found that the Westergren ESR of 40 to 70 mm/h was markedly accelerated in HD patients compared with a top normal value of 25 mm/h [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there have been only a few reports on the ESR in this population [3, 4, 5, 6]. All of them, except one [5], found that the Westergren ESR of 40 to 70 mm/h was markedly accelerated in HD patients compared with a top normal value of 25 mm/h [7]. However, none of these studies [1, 2, 3, 4, 5, 6]considered the fact that anemia, which accompanies renal failure, is one of the main factors responsible for accelerated ESR [8].…”
Section: Introductionmentioning
confidence: 99%